2015
DOI: 10.1097/hrp.0000000000000058
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Co-occurring Anxiety Disorders and Substance Use Disorders

Abstract: Anxiety disorders co-occur with substance use disorders at a high rate in both the general population and in treatment-seeking samples. The co-occurrence of these disorders is associated with greater symptom severity, higher levels of disability, and poorer course of illness relative to either disorder alone. However, relatively little research focus has been afforded to the treatment of co-occurring anxiety and substance use disorders. This notable gap in the research literature may not only leave anxiety unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 123 publications
0
41
0
Order By: Relevance
“…First, we found that TBI was an effective intervention for reducing harmful drug and alcohol use, as well as co‐occurring anxiety symptoms, among ED patients. These results indicate that successfully intervening on drug use can positively impact comorbid alcohol use and anxiety symptoms, suggesting that concurrent or integrated treatments for anxiety‐related problems may not be necessary for some individuals . Although CBI reduced cannabis use days when examined as a sole outcome , CBI relative to EUC did not result in significant reductions in severity of alcohol use, cannabis use and anxiety when examined as simultaneous outcomes.…”
Section: Discussionmentioning
confidence: 87%
“…First, we found that TBI was an effective intervention for reducing harmful drug and alcohol use, as well as co‐occurring anxiety symptoms, among ED patients. These results indicate that successfully intervening on drug use can positively impact comorbid alcohol use and anxiety symptoms, suggesting that concurrent or integrated treatments for anxiety‐related problems may not be necessary for some individuals . Although CBI reduced cannabis use days when examined as a sole outcome , CBI relative to EUC did not result in significant reductions in severity of alcohol use, cannabis use and anxiety when examined as simultaneous outcomes.…”
Section: Discussionmentioning
confidence: 87%
“…Having a peer on the treatment team of patients with co-occurring disorders was associated with better fidelity to treatment plans, more engagement in care (e.g., outpatient care after hospital discharge), and better outcomes (e.g., reduced substance use and mental health symptoms) (Harrison et al, 2017; O’Connell et al, 2017). Further, to enhance use of outpatient treatments after hospital discharge, new integrated treatments should continue to be developed and tested, such as cognitive behavioral therapies for co-occurring substance use and anxiety disorders (McHugh, 2015; McHugh et al, 2017), and combined behavioral and pharmacotherapies for alcohol use disorders and depression (Samakhvalov et al, 2017). …”
Section: Discussionmentioning
confidence: 99%
“…Our findings are of clinical relevance and indicate that being a smoker during the first month of substance use treatment is associated with a significant increase in the odds of substance use relapse at follow‐up. Our analytic approach accounted for a number of demographic and psychosocial factors that are known to be associated with substance use treatment outcomes (Carpenter, Schreiber, Church, & McDowell, ; Hser, Huang, Teruya, & Douglas Anglin, ; Ilgen, Tiet, & Moos, ; Kelly, Finney, & Moos, ; Lydecker et al., ; McHugh, ). Findings demonstrate that smoking status maintains its effect above and beyond the control variables in our logistic model, which underscores the robust nature of the relationship.…”
Section: Discussionmentioning
confidence: 99%